Enhanced transport of dissolved methane from the Chukchi Sea to the Central Arctic - Ye, Wangwang; Li, Yuhong; Wen, Jianwen; Zhang, Jiexia; Shakhova, Natalia; Liu, Jian; Wu, Man; Semiletov, Igor P.; Zhan, Liyang (Global biogeochemical cycles)
Rising temperatures in the Arctic Ocean can cause considerable changes, such as decreased ice cover and increased water inflow from the Pacific/Atlantic sector, which may alter dissolved methane (CH4) cycles over the Arctic Ocean. However, the fate of dissolved CH4 in the Arctic remains uncertain. Here, we show that CH4 in the Chukchi Sea is enhanced in the shelf/slope areas, stored in the Upper Halocline (UHC), and transported to the central Arctic, contributing to the CH4 excess (ΔCH4) in the basins. The concentration of ΔCH4 in the UHC was increasing (0.1 nM per year) and the ΔCH4 has been distributed deeper and farther in the last decade than in the 1990s because of the intensification of Pacific water inflow due to oceanographic (currents) and atmospheric forcings (winds). We found heterogeneous CH4 (208.4% ± 131.7%) in the Polar Mixed Layer and CH4 supersaturation (1,100.9%–1,245.4%) in the below-ice seawater in the basins, which may indicate the effect of sea ice cycles with the support of sediment-origin CH4. We estimate the sea-to-air flux to be 1.1–2.4 μmol CH4 m −2 day −1 during the ice-free period in the Chukchi Sea, which suggests that the Chukchi Sea is currently a minor source (0.003 Tg in summer) of atmospheric CH4. Taken together, we propose a bottom-up mechanism for CH4 transport and emission and are concerned that the increases in the concentration of ΔCH4 and the transport distance/rate of ΔCH4 plume are occurring, with the potential to affect CH4 emissions in the Pacific sector of the Arctic Ocean.